2021
DOI: 10.1097/mcp.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of radiological imaging in cystic fibrosis

Abstract: Purpose of reviewRadiological imaging has a crucial role in pulmonary evaluation in cystic fibrosis (CF), having been shown to be more sensitive than pulmonary function testing at detecting structural lung changes. The present review summarizes the latest published information on established and evolving pulmonary imaging techniques for assessing people with this potentially life-limiting disorder. Recent findingsChest computed tomography (CT) has taken over the predominant role of chest radiography in many ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…While for CT this should be focus on the introduction of an ultra-low-dose CT protocol (i.e. radiation dose in the range of a CR), for MRI will need both international agreement on a common set of MRI sequences and development of dedicated post-processing tools for quantification of MRI findings [167]. The authors' recommendation is, therefore, to maintain routine follow-up of patients who improve under the effects of CFTR modulation; on the other hand, any significant deterioration of lung function, or clinical symptoms, should prompt further imaging investigation either with ultra-low dose CT or chest-MRI according CF centre expertise.…”
Section: First Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…While for CT this should be focus on the introduction of an ultra-low-dose CT protocol (i.e. radiation dose in the range of a CR), for MRI will need both international agreement on a common set of MRI sequences and development of dedicated post-processing tools for quantification of MRI findings [167]. The authors' recommendation is, therefore, to maintain routine follow-up of patients who improve under the effects of CFTR modulation; on the other hand, any significant deterioration of lung function, or clinical symptoms, should prompt further imaging investigation either with ultra-low dose CT or chest-MRI according CF centre expertise.…”
Section: First Diagnosismentioning
confidence: 99%
“…Studies have shown that dose variation between specialist centres strongly contributes to a huge variability of cumulative dose, which has prompted the introduction of uniform dose-management strategies [15,29]. Recent developments have also shown the potential for further dose reduction, up to 78%, using optimised imaging protocols, with iterative reconstruction techniques via the newest generation CT scanners [35,36,44,158,160,167]. Interestingly, these optimised CT protocols have allowed the availability of diagnostic quality CT images at a dose equivalent of a CR, while demonstrating superior sensitivity to the CR and equivalent standard CT in the detection of bronchiectasis [160].…”
Section: First Diagnosismentioning
confidence: 99%
“…CF typically presents on chest CT with bilateral bronchiectasis that dominates in the upper lung lobes, bronchial wall thickening, mucus plugging, emphysema, air trapping, atelectasis, acinar nodules, thickening of interlobular and intralobular septa as well as areas of ground glass opacities [ 16 , 18 ]. It was recommended to perform chest CT biennially in stable CF patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Convincing results from multicentre studies using a fully automated commercially available AI-based image analysis system [38] and the upcoming introduction of commercially available software for CF CT imaging [16] are expected to change clinical trial design and clinical practice. Paediatric radiologists need to have indepth knowledge of these new tools to be able to interpret their results for providing an objective assessment of CF lung disease status to the clinician [14]. may survive the challenge of CT if its sensitivity can be enhanced by dedicated automatic AI-based scoring systems.…”
Section: Moving From Qualitative To Quantitative Imagingmentioning
confidence: 99%
“…The latter is an important criterion in a large paediatric population such as that of people with CF. The introduction of low-dose and ultra-low-dose chest CT protocols has challenged the use of chest radiography, which has been replaced by CT at some specialised centres [ 14 ]. The use of CT instead of chest radiography has also been promoted by its higher sensitivity and specificity for early and subtle changes in CF lung disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%